ENHANCING SCIENTIFIC REASONING SKILLS THROUGH SELF-DIRECTED LEARNING MANAGEMENT IN BIOLOGY AMONG GRADE 11 STUDENTS - Detburam, Phutawan; Udomphol, Boonrudee; Rattanakorn, Pawinee (Journal of Educational Review Faculty of Education in MCU, 2026)
This study aimed to enhance scientific reasoning skills through self-directed learning management in Biology among Grade 11 students, as compared to a 70 percent criterion. The study employed a quasi-experimental research design using a one-group pretest–posttest design, with the results evaluated against the specified criterion. The sample consisted of 42 Grade 11 students from Song-Phi-Nong Wittaya School during the second semester of the 2025 academic year, selected through simple random sampling. The research instruments included: (1) self-directed learning management lesson plans and (2) a scientific reasoning skills test. The research instruments consisted of (1) self-directed learning management plans, and (2) a scientific reasoning skills assessment instrument. The data were analyzed using statistical methods, including mean, standard deviation, the dependent samples t-test, and comparison with the percentage criterion. The results revealed that the students’ posttest mean score on scientific reasoning skills was 27.12, which exceeded the 70 percent criterion (24.50 out of the total score). The one-sample t-test yielded a t-value of 3.92, demonstrating that the posttest scores were significantly higher than the established criterion at the .05 level of significance. The findings suggest that self-directed learning management is effective in enhancing scientific reasoning skills in Biology. Students actively participated in setting learning goals, planning, implementing, and evaluating their own learning processes, which contributed to improvements in analytical thinking, logical reasoning, and systematic scientific conclusion skills.